How IFRS 9 has impacted Deferred Tax Assets and Bank Regulatory Capital in South Africa - Abuka, Kevin (Department of Finance and Tax, 2024)
Gallemore (2012) empirically proved that banks with larger percentages of deferred tax assets in their regulatory capital are more likely to fail and have higher credit risk. However, following the application of IFRS 9 from January 2018, there arose an increasing likelihood that deferred tax assets included in bank regulatory capital would increase. This was due to the expected credit loss model utilised by IFRS 9 while provisioning for loan losses. The model means that credit impairments are larger and recognised earlier. As a result, deferred tax assets likely increase. This study sought to ascertain whether 1) the nature of the relationship between credit impairments due to loans and deferred tax assets has changed to a stronger positive corelation in the post IFRS 9 era and 2) deferred tax assets are displacing better forms of capital within banks' regulatory capital. The results of the study show that deferred tax assets are increasing in line with credit impairments due to loans in the post IFRS 9 era. Additionally, deferred tax assets arising due to temporary differences make up a larger component of regulatory capital in the post IFRS 9 era. Findings from the study can contribute to the reinforcement and revision of prudential policy set by regulators within the banking sector to ensure that banks maintain sufficient capital adequacy levels.